Dynamic behaviour of transition zones in soft soils during regular train traffic. (March 2018) - Zuada Coelho, Bruno; Priest, Jeffrey; Hölscher, Paul
Transition zones in railway tracks are of importance for infrastructure managers, due to the high maintenance required to maintain appropriate track geometry. To improve our understanding of the performance of transition zones, a research program was conducted in The Netherlands, in which a transition zone was extensively monitored during regular train traffic. This paper presents some of the results from the monitoring of this transition zone. The results highlight the poor performance of this transition zone compared to its expected design performance. The track was found to be hanging over the transition zone, exhibiting a rocking motion about a culvert. Track stiffness was found to reduce linearly with increasing train speed. The implications on the design of transition zones are discussed, with recommendations made.